Techno-Economic Assessment for CO2 Capture From Air Using a Conventional Liquid-Based Absorption Process - Kiani, Ali; Jiang, Kaiqi; Feron, Paul (Frontiers in Energy Research, 2020)
Carbon dioxide (CO2) capture of directly from ambient air in a conventional monoethanolamine (MEA) absorption process was simulated and optimised using a rate-based model in Aspen Plus. The process aimed to capture a specific amount (148.25 Nm3/h) of CO2 from the air, which was determined by a potential application aiming to produce synthetic methane from the output of a 2.7 MW electrolyser. We conducted a sensitivity analysis around different parameters such as air humidity, capture rate, CO2 loading and reboiler temperature, and evaluated the energy consumption and overall cost in this system. To meet the design requirement for standard packed columns, the rich absorption liquid was circulated to the top of the absorber. A capture rate of 50% was selected in this process as a baseline. At higher capture rates, the required energy per tonne of captured CO2 increases and at lower capture rates, the size of equipment, in particular, absorber and blowers increases due to the need for processing a significantly larger volume of air at the given CO2 production volume. At the base case scenario, a reboiler duty of 10.7 GJ/tCO2 and an electrical energy requirement of 1.4 MWh/tCO2 were obtained. The absorber diameter and height obtained were 10.4 and 4.4 m, respectively. The desorber is found to be relatively small at 0.54 m in diameter and 3.0 m in height. A wash water section installed at top of the absorber decreased the MEA loss to 0.28 kg/tonne CO2. However, this increased capital cost by around 60% resulting in CO2 capture costs of 1691 per tonne CO2 for the MEA base scenario. Based on the techno-economic analysis, assuming a non-volatile absorbent rather than MEA thereby avoiding a wash water section, and using an absorption column built from cheaper materials, the estimated cost per tonne of CO2 produced was reduced to 676/tCO2. The overall cost range was between 273 and 1227 per tonne of CO2 depending on different economic parameters In order to reduce the cost further, the use of innovative cheap gas-liquid contactors that operate at lower liquid to gas ratios is crucial.